The universal encyclopedia of machines (London, 1972)
This book introduce simplest mechanical functions of modern life to the most basic scientific principles and comples industrial processes that affect our well-being. The result is, we believe, a unique book - a graphic and original introduction to the mothern world of technology.
Keywords: Công nghệ,Technology